Инфузионная терапия сепсиса при травме стопы у больных сахарным диабетом - Трибушной, О. В.; Кляцкий, Ю. П.; Труфанов, И. И.; Банит, О. В.; Tribushnoj, O. V.; Klyatsky, Y. P.; Trufanov, I. I.; Banit, O. V.; Трибушний, Олег Володимирович; Кляцький, Юрій Пантелійович; Труфанов, Іван Іванович (My University, 2019)
Цель исследования. Разработать схемы инфузионной терапии сепсиса при гнойных осложнениях переломов костей стопы у больных сахарным диабетом. Изучены результаты лечения 22 больных сахарным диабетом с травмами стопы, которые осложнились гнойно-воспалительным процессом и сепсисом. С целью восстановления нарушений гомеостаза больные получали комплекс лечебных мероприятий включая оперативное лечение, инфузионную терапию, иммунотерапию, антибиотикотерапию. Больные находились под постоянным контролем эндокринолога. Использование разработанной лечебной тактики позволило улучить результаты лечения больных сахарным диабетом с травматологическим сепсисом. Purpose of the study. Develop schemes for infusion therapy of sepsis with purulent complications of fractures of the foot bones in patients with diabetes mellitus. In order to restore disorders of homeostasis, patients received a complex of medical measures including surgical treatment, infusion therapy, immunotherapy, antibiotic therapy. The results of treatment of 22 diabetic patients with foot injuries that were complicated by purulent-inflammatory process and sepsis were studied. The patients were under the constant control of the endocrinologist. The use of the developed medical tactics allowed improving the results of treatment of patients with diabetes with traumatic sepsis.
Infusion therapy of sepsis in trauma in patients with diabetes mellitus
Keywords: сепсис; полиорганная недостаточность; операция; инфузионная терапия; sepsis; multiple organ failure; surgery; infusion therapy